Resistance Exercise in a Hot Environment Alters Serum Markers in Untrained Males - Eskandari, Arezoo; Fashi, Mohamad; Saeidi, Ayoub; Boullosa, Daniel; Laher, Ismail; Ben Abderrahman, Abderraouf; Jabbour, Gerorges; Zouhal, Hassane (Frontiers in Physiology, 2020)
Purpose We examined the effects of moderate resistance exercise (RE) on serum cortisol, testosterone, extracellular heat shock protein (HSP70), interleukin (IL)-6 and IL-15 concentrations in untrained males in a hot environment. Methods Ten untrained young males (26 ± 3 years; 75.8 ± 6 kg; 177.4±5.3 cm) performed two series of full body RE (3 sets of 8 to 10 repetitions, 30-60 s recovery between series with 70% of one maximal repetition (1-RM), with a rest period of 1 to 3 min between exercises) performed in a random order in both heated ( 35ºC) and thermoneutral (22ºC) conditions. Serum concentrations of testosterone, cortisol, HSP70, IL-6 and IL-15 were measured before, at the end, and 1-h after RE sessions. Participants in both groups consumed 4 ml of water/kg body mass every 15 min. Results There were time-related changes in testosterone, HSP70, IL-6 (P<0.001); and cortisol and IL-15 (P<0.05). Levels of cortisol, HSP70, and IL-6 increased immediately for RE at 35ºC, and testosterone and IL-15 levels were decreased. Changes in serum testosterone, HSP70, cortisol, IL-15 and IL-6 levels were reversed after 1-h. A significant time × condition interaction was observed for IL-15, HSP70 (P<0.001); cortisol and IL-6 (P<0.05), but not for testosterone (P>0.05). Conclusion RE in a heated environment may not be appropriate for achieving muscle adaptations due to acute changes of hormonal and inflammatory markers.